Splenectomy Correlates With Increased Risk of Acute Pancreatitis: A Case-Control Study in Taiwan - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu (Journal of epidemiology, 2016)
The objective of the study was to investigate the association between splenectomy and acute pancreatitis. We conducted a case-control study using the database of the Taiwan National Health Insurance Program. We included 7666 subjects aged 20-84 years with first-time acute pancreatitis during the period of 1998-2011 as cases and 30 664 randomly selected subjects without acute pancreatitis as controls. Both cases and controls were matched for sex, age, and index year of acute pancreatitis diagnosis. The association of acute pancreatitis with splenectomy was examined using a multivariable unconditional logistic regression model and reported as an odds ratio and its 95% confidence interval (CI). After adjustment for covariables, the adjusted odds ratio of acute pancreatitis was 2.90 for subjects with splenectomy (95% CI, 1.39-6.05) compared with subjects without splenectomy. Splenectomy is associated with acute pancreatitis. Further studies are necessary to clarify the underlying mechanism.